The e-commerce sales tax: a case study of Thailand - Udomvitid, Kalaya, author; Fan, Chuen-mei, advisor; Mushinski, David, committee member; Fan, Liang-Shing, committee member; Olienyk, John, committee member (Colorado State University. Libraries, 2003)
The increase in commercial transactions by electronic means or e-commerce has concerned many governments because of lost tax revenues due to e-commerce. There is a difficulty in including e-commerce transactions in the general sales tax base, if agents and products dealing with e-commerce are in digital forms. The governments have realized that they have to minimize such tax losses, particularly the sales tax. Imposition of a new tax targeted at Internet sales is a method to prevent tax losses. However, based on optimal tax theory, preventing tax losses is not a sufficient reason for a government to decide to add a new e-commerce tax on the existing tax system. This study illustrates that criteria such as efficiency, equity, administrative costs, and technology feasibility which should be used to assess an e-commerce tax. This study applies such criteria to assess the e-commerce tax in developing countries by using Thailand as a case study. After weighing the criteria, this study suggests that an e-commerce tax should not be imposed in Thailand in the next few years. This study also demonstrates that there has been only a small amount of sales tax that has been lost from e-commerce in recent years. If the e-commerce transactions are exempted from sales tax, the tax loss is less than 1 % of total tax revenues by 2004. Nevertheless, the tax losses would increase significantly in the future. The study recommends that the Thai government needs to revise the existing tax rules to prevent the tax losses and keep tax neutrality between traditional and electronic commerce. Moreover, to facilitate policy-making decision concerning e-commerce, including tax policies, data gathering is the most important task of the Thai government.
Keywords: studies; software; computer peripherals; websites